2015
DOI: 10.1513/annalsats.201410-469bc
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Use of Loop Gain Measures to Determine Continuous Positive Airway Pressure Efficacy in Patients with Complex Sleep Apnea. A Pilot Study

Abstract: Rationale: Measures of unstable ventilatory control (loop gain) can be obtained directly from the periodic breathing duty ratio on polysomnography in patients with Cheyne-Stokes respiration/ central sleep apnea and can predict the efficacy of continuous positive airway pressure (CPAP) therapy.Objectives: In this pilot study, we aimed to determine if this measure could also be applied to patients with complex sleep apnea (predominant obstructive sleep apnea, with worsening or emergent central apneas on CPAP). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…a CPAP titration versus those with resolved CSR [5]. Furthermore, a higher loop gain on CPAP, in patients without heart failure, predicts CSR persistence with continued CPAP treatment over time [13].…”
Section: Lgtherapymentioning
confidence: 99%
“…a CPAP titration versus those with resolved CSR [5]. Furthermore, a higher loop gain on CPAP, in patients without heart failure, predicts CSR persistence with continued CPAP treatment over time [13].…”
Section: Lgtherapymentioning
confidence: 99%
“…[1][2][3][4] Treatment with positive airway pressure (PAP) is highly efficacious because it generally eliminates respiratory events in adherent patients. 5 However, the effectiveness of PAP is limited by varying adherence to treatment. 6,7 Although the data vary, they suggest that PAP adherence may be optimized by using labor-intensive approaches such as detailed support and education.…”
mentioning
confidence: 99%
“…Although there have been multiple and more sophisticated techniques to 22,23 we have used the Sand formula that can be calculated readily from the sleep parameters collected by portable monitoring technology. 24 As was published by Ainslie et al, the central apnea duration tends to shorten as the altitude increases. 20 Moreover, Lombardi et al found that males had more central apneas regardless of the level of altitude when compared to female subjects.…”
Section: Discussionmentioning
confidence: 67%